Adverse reproductive outcomes and occupational exposures among nurses: an investigation of multiple hazardous exposures. - McAbee RR; Gallucci BJ; Checkoway H (AAOHN Journal, 1993)
The increasing numbers of pregnant women and women of childbearing age who are employed and exposed to hazardous substances pose occupational health concerns. The findings of this study indicate the importance of not minimizing concern about exposure to radiation. Radiation monitoring should be implemented to a greater extent, and methods to measure low dose chronic radiation exposure should be developed. Synergy between the adverse reproductive effects from multiple workplace factors among nurses, including but not limited to radiation, video display terminal use, and chemotherapeutic agents, warrants further evaluation.